Analysis of predictors of mortality and clinical outcomes of different subphenotypes for moderate-to-severe pediatric acute respiratory distress syndrome: A prospective single-center study - Wang, Qingyue; Liu, Yanling; Fu, Yueqiang; Liu, Chengjun; Li, Jing; Dang, Hongxing (Frontiers in Pediatrics, 2022)
Backgroud: This study aimed to observe the prognosis of patients with moderate-to-severe pediatric acute respiratory distress syndrome (PARDS) admitted to the Pediatric Intensive Care Unit (PICU) as a function of underlying conditions and available treatment strategies, and to investigate the risk factors for death and the outcomes of different clinical subphenotypes. Methods: Patients were divided into non-survivors and survivors according to the prognosis 28 days after the diagnosis. The risk factors for death and the predictive value of relevant factors for mortality were analyzed. Latent class analysis was used to identify different clinical subphenotypes. Results: A total of 213 patients with moderate-to-severe PARDS were enrolled, of which 98 (46.0%) died. Higher PELOD2 scores (OR = 1.082, 95% CI 1.004–1.166, p < 0.05), greater organ failure (OR = 1.617, 95% CI 1.130–2.313, p < 0.05), sepsis (OR = 4.234, 95% CI 1.773–10.111, p < 0.05), any comorbidity (OR = 3.437, 95% CI 1.489–7.936, p < 0.05), and higher infiltration area grade (IAG) (OR = 1.980, 95% CI 1.028–3.813, p < 0.05) were associated with higher mortality. The combination of these five indicators had the largest area under the curve (sensitivity 89.79%, specificity 94.78%). Patients were classified into higher-risk and lower-risk phenotype group according to the latent class analysis. Compared to the lower-risk phenotype, more patients with higher-risk phenotype suffered from sepsis (24.40% vs. 12.20%, p < 0.05), inherited metabolic diseases (45.80% vs. 25.60%, p < 0.05), positive respiratory pathogens (48.10% vs. 26.80%, p < 0.05), and higher IAG (p < 0.05); they also had significantly higher PIM3 and PELOD2 scores (p < 0.05), with an extremely high mortality rate (61.1% vs. 22.0%, p < 0.05). Conclusions: Moderate-to-severe PARDS has high morbidity and mortality in PICU; a higher PELOD2 score, greater organ failure, sepsis, any comorbidity, and higher IAG were risk factors for death, and the combination of these five indicators had the greatest value in predicting prognosis. More patients with sepsis, positive respiratory pathogens, higher PIM3 and PELOD2 scores, and higher IAG were in higher-risk phenotype group, which had worse outcomes. Clear classification facilitates targeted treatment and prognosis determination.